Leadership Skills Required to Lead a Team and Manage an Organization Effectively - Safitri, Dika; Rahira, Natasya; Kamarudin, Syamsu A (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This article discusses the key leadership skills required in an entrepreneurial context to lead a team and manage an organization effectively. Leadership in entrepreneurship has unique characteristics compared to conventional organizations, because it demands high flexibility, innovation, and the ability to face uncertainty. Based on a literature review of several books and journals, core skills such as communication, decision making, team empowerment, and time and crisis management skills are considered essential. This article aims to provide an in-depth understanding of leadership skills that are relevant for modern entrepreneurs in order to improve organizational performance in a sustainable manner. The aim of this research is also to find out the leadership skills needed to lead a team and manage an organization effectively.  The type of research carried out is literature study, which aims to collect books and data and other written information related to the discussion of the problem being studied.  Data sources from books, magazines and articles. Team leadership is a person's ability to direct, guide and coordinate team members to achieve common goals agreed upon by the organization. This journal explores the crucial concept of leadership in the context of entrepreneurship, especially in leading teams and managing organizations effectively to achieve company goals. Through literature analysis and case studies, this journal identifies several key leadership skills, such as vision and strategy, communication, collaboration, motivation, and adaptation. This journal also discusses how these skills can be applied in building solid teams, managing sustainable organizations, and achieving success in the world of entrepreneurship, as well as the challenges faced by leaders, strategies for achieving goals, stages of team leadership, and various team leadership models that can be applied in practice.